Evaluation Of Antibacterial Synergy Of Polyalthia Longifolia (Sonn.) Leaf Ethyl Acetate Fraction (Pleaf) With Ampicillin Against Methicillin-Resistant Staphylococcus Aureus (Mrsa) - Balasupramaniam, Kirubakari (2019)
Polyalthia longifolia which originates from India is rich with various useful phytochemicals which are valuable for human health. The aim of the study is to evaluate whether the combination of Polyalthia longifolia ethyl acetate fraction (PLEAF) and ampicillin exhibits synergistic antimicrobial activity against methicillin-resistant Staphylococcus aureus (MRSA) bacteria followed by their antioxidant capacity and their cytotoxicity level. The evaluation of synergistic activity of PLEAF fraction and ampicillin against MRSA local isolate was conducted with various antimicrobial assays namely disc diffusion method, minimum inhibitory concentration (MIC), minimum bactericidal concentration (MBC), fractional inhibitory concentration (FIC), time-kill study and scanning electron microscopy (SEM). The combinational effect of PLEAF fraction and ampicillin exhibited significant antibacterial activity against MRSA. This is proven when the MIC values of PLEAF fraction (62.5 μg/mL) and ampicillin (5000 μg/mL) were found to decrease to 15.63 μg/mL for PLEAF and 2500 μg/mL for ampicillin respectively in the FIC assay against the MRSA bacteria. The 2,2-diphenyl-1-picrylhydrazyl (DPPH) and nitric oxide free radical scavenging activities showed that PLEAF fraction possessed high antioxidant activity and the combinational of PLEAF fraction and ampicillin exhibited moderate antioxidant activity. The usage of PLEAF fraction with high antioxidants activity is important to prevent the adverse effect of the production of an excessive amount of free radicals during microbial infection.